Coerência e epieikeia : fundamentos de uma decisão praeter legem - Silva, Matheus Teixeira da (2017)
The dissertation aims at assessing the possibility of a praeter legem decision, thus understanding the decision that does not apply the normative consequent even acknowledging the effective fulfillment of the factual support (normative antecedent). The investigation begins from an evolutionary and conceptual analysis of the legal positivism, standing out their divergence to the antagonistic thesis of the natural law. In the sequence, already under the contemporary framework of legal positivism, the importance of the coherent conception of the law stands out, whose objective is the analysis of the articulation between the elements that make up the legal system. Thus, the theme of coherence is exposed from different perspectives, especially the readings of unity (Canotilho), system (Canaris) and integrity (Dworkin). Such information gives an account of the need to understand the legal order as a unit of meaning in order to avoid interpretations of the rules out of their context, a true presupposition of our central argument. This development leads to the study of the possibility of a praeter legem decision according to the notion of epieikeia (equity) in the Aristotelian tradition, proceeding to the analysis of the institute and a critical attempt of conceptualization, highlighting the problem of the generality of the law and the singularity of the cases. Still, the epieikeia is briefly seen in the work of Thomas Aquinas. On the basis of these elements, it is hoped to justify the possibility of a praeter legem decision in the current conjuncture of the philosophy of law, working with the idea of exception of the rules and based on the search for a coherence of the legal-normative order that may justify a punctual disobedience to the law. Finally, a small analysis is made on judicial discretion and its necessary limitation due to the normative framework. Furthermore, the use of deductivism as legal reasoning is discussed.